How Tax Policy and Incentives Affect Foreign Direct Investment : A Review - Morrisset, Jacques; Pirnia, Neda (World Bank, Washington, DC, 2014)
With an increasing number of governments competing to attract multinational companies, fiscal incentives have become a global trend that has grown considerably in the 1990s. Poor African countries rely on tax holidays, and import duty exemptions, while industrial Western European countries allow investment allowances, or accelerated depreciation. Have governments offered unreasonably large incentives to entice firms to invest in their countries? The authors review the literature on tax policy, and foreign direct investment, and explore possibilities for research. They observe that tax incentives neither make up for serious deficiencies in a country's investment environment, nor generate the desired externalities. Long-term strategies to improve human, and physical infrastructure - and, where necessary, to streamline government policies and procedures - are more likely than incentives to attract genuine long-term investment. But more recent evidence has shown that when other factors - such as infrastructure, transport costs, and political and economic stability - are more or less equal, the taxes in one location may have a significant effect on investors' choices. This effect is not straightforward, however. It may depend on the tax instrument used by the authorities, the characteristics of the multinational company, and the relationships between the tax systems in the home country, and recipient countries. For example, tax rebates are more important for mobile firms, for firms that operate in multiple markets, and for firms whose home country exempts any profit earned abroad (Canada, France) rather than using tax credit systems (Japan, the United Kingdom, the United States). Even if tax incentives were quite effective in increasing investment flows, the costs might well outweigh the benefits. Tax incentives are not only likely to have a negative direct effect on fiscal revenues, but also frequently create significant opportunities for illicit behavior by tax administrators, and companies. This issue has become crucial in emerging economies, which face more severe budgetary constraints, and corruption than industrial countries do. The authors suggest research in five areas: 1) The eventual non-linear impact of tax rates on the investment decisions of multinational companies. 2) the effect of tax policy on the composition of foreign direct investment (for example, green-field, reinvested earnings, and mergers and acquisitions). 3) The development of new technologies, and global companies that are likely to be more sensitive to, and able to exploit incentives. 4) The need for a global approach to the taxation of multinational companies. 5) The question of whether tax incentives should be directed only at (foreign) investors that make the "right things" (such as environmentally safe products) or more broadly at those that bring jobs, technology transfers, and marketing skills.